THE USING OF AUTHENTIC TEXTTO INCREASESTUDENTS READING COMPREHENSION ACHIEVEMENT - Helmi Syukur (Baruga: Jurnal Ilmiah, 2022)
Responding to the fact that reading is still difficult to be mastered by students, it demands teachers to develop their teaching material in order to help them to achieve the goal of teaching reading. In this study, the researcher used authentic text as a supported material to teach reading. The subject of the research was first semester students of English Literature Students of UIN Alauddin Makassar. Descriptive qualitative was conducted as the design of this research. In this researcher, the researcher collected the data from gathering documentary evidence, questionnaire and conducting interviews. Then, questionnaire and interview was conducted since the researcher wanted to know the students’ response toward the using of authentic literature in teaching reading. As result, it can be concluded that authentic text could be used as an appropriate supported material in teaching reading comprehension. The researcher suggests the teacher to be more creative in giving and applying the other material to teach reading. For other researchers, this study is far from perfect. Other research in the same discussion will give contribution to the teaching of reading that can be used as a supported material. Menanggapi fakta bahwa keterampilan membaca masih sulit dikuasai oleh siswa, pengajar dituntut untuk mengembangkan materi pengajaran mereka untuk membantu mencapai tujuan pengajaran membaca. Dalam penelitian ini, peneliti menggunakan teks asli sebagai bahan pendukung untuk mengajarkan pembacaan. Subjek penelitian adalah siswa semester I Sastra Inggris UIN Alauddin Makassar. Metode deskriptif kualitatif dilakukan sebagai rancangan penelitian ini. Dalam penelitian ini, peneliti mengumpulkan data dari pengumpulan bukti dokumenter, kuesioner dan wawancara. Kuesioner dan wawancara dilakukan karena peneliti ingin mengetahui tanggapan siswa terhadap penggunaan teks asli dalam pengajaran membaca. Kesimpulannya, bahwa teks asli dapat digunakan sebagai bahan pendukung yang sesuai dalam mengajarkan pemahaman bacaan. Peneliti menyarankan agar pengajar lebih kreatif dalam memberi dan menerapkan materi lain untuk diajarkan dalam kelas membaca. Bagi peneliti lain, penelitian ini jauh dari sempurna. Penelitian lain dalam diskusi yang sama akan memberikan kontribusi terhadap pengajaran membaca yang bisa dijadikan bahan pendukung.